Combination Therapy Is Superior to Sequential Monotherapy for the Initial Treatment of Hypertension: A Double‐Blind Randomized Controlled Trial - MacDonald, Thomas M.; Williams, Bryan; Webb, David J.; Morant, Steve; Caulfield, Mark; Cruickshank, J. Kennedy; Ford, Ian; Sever, Peter; Mackenzie, Isla S.; Padmanabhan, Sandosh; McCann, Gerald P.; Salsbury, Jackie; et al. (Journal of the American Heart Association, 2017)
Background Guidelines for hypertension vary in their preference for initial combination therapy or initial monotherapy, stratified by patient profile; therefore, we compared the efficacy and tolerability of these approaches. Methods and Results We performed a 1‐year, double‐blind, randomized controlled trial in 605 untreated patients aged 18 to 79 years with systolic blood pressure (BP) ≥150 mm Hg or diastolic BP ≥95 mm Hg. In phase 1 (weeks 0–16), patients were randomly assigned to initial monotherapy (losartan 50–100 mg or hydrochlorothiazide 12.5–25 mg crossing over at 8 weeks), or initial combination (losartan 50–100 mg plus hydrochlorothiazide 12.5–25 mg). In phase 2 (weeks 17–32), all patients received losartan 100 mg and hydrochlorothiazide 12.5 to 25 mg. In phase 3 (weeks 33–52), amlodipine with or without doxazosin could be added to achieve target BP. Hierarchical primary outcomes were the difference from baseline in home systolic BP, averaged over phases 1 and 2 and, if significant, at 32 weeks. Secondary outcomes included adverse events, and difference in home systolic BP responses between tertiles of plasma renin. Home systolic BP after initial monotherapy fell 4.9 mm Hg (range: 3.7–6.0 mm Hg) less over 32 weeks (P<0.001) than after initial combination but caught up at 32 weeks (difference 1.2 mm Hg [range: −0.4 to 2.8 mm Hg], P=0.13). In phase 1, home systolic BP response to each monotherapy differed substantially between renin tertiles, whereas response to combination therapy was uniform and at least 5 mm Hg more than to monotherapy. There were no differences in withdrawals due to adverse events. Conclusions Initial combination therapy can be recommended for patients with BP >150/95 mm Hg. Clinical Trial Registration URL: http://www.ClinicalTrials.gov. Unique identifier: NCT00994617.